Life cycle of a Butterfly - Conolly, Cathryn (New Delhi The Energy Resource Institute, 2011)
The butterfly starts its life as a tiny egg and goes through a slow and magical process of changing into a butterfly. Where does the butterfly lay its eggs? What are the stages in between? How long does it take for a butterfly to emerge? This book not only explains the amazing metamorphosis that takes place in the life cycle of a butterfly, it also contains many interesting facts about this beautiful creature.
Keywords: Butterfly